Direito e justiça durante o reinado dos Reis Católicos: análise à luz das Ordenanzas Reales de Castilla - Moi, Fernanda de Paula Ferreira (2016)
This thesis brings in its speech the concepts of law and justice prevailing during the reign of the Catholic Kings, as well as the current law at the time, in particular the Ordenanzas Reales de Castilla. Isabel of Castile and Fernando of Aragon, also known as the Catholic Monarchs, joined in marriage in the year 1469, unified the kingdoms and implemented reforms in the legal system and existing institutions, but Castile fit the central role of this new political unit. Given this reality, although the sovereign power was exercised by both monarchs, the common form, the basic elements of each kingdom - territories Fueros and Cortes - were kept. It can be inferred that, with that union, Isabel and Fernando developed a centralized project on concepts of law and Justice, with the fundamentals the Aristotelian-Thomistic principles, acting thus as judges and legislators, in order to strengthen the system legal and to apply and distribute Justice to inflows from their territories. Thus, both restored the political and social order and the reformed institutions of government and Justice in Castile, promoting the centralization of power. In this context, were highlighted the concepts of law and Justice prevailing at the time of the Catholic Kings, the way legislating and thought, as well as the legal system, in particular the Ordenanzas Reales de Castilla.